Pendidikan Teknologi Menurut Al-Quran dan Hadis - Heru Triastanawa; Charles Charles (Moral : Jurnal kajian Pendidikan Islam, 2025)
It has become common for everyone to judge Islamic Religious Education learning as unsuccessful. Either from themselves or when measuring others. There is a lot of evidence such as various criminal acts, criminality or serious violations both seen directly or through digital media. When viewed from the perspective of education or Islamic religion, and also Islamic religious education. One of the statements is that the learning method or system is not optimal and does not or is lacking in the use of existing digital technology media, so that learning becomes boring. Therefore, it is fitting that an educator must be innovative and creative when providing learning so that it can become an interest and enthusiasm for students when learning, especially Islamic Religious Education learning, although this is an important subject but in general it is not as interesting as other subjects. If successful, the values ​​of Islam in the world of education can be conveyed and even realized by being applied to personal and general life in society. One of them is utilizing technological advances in the current era, especially as a mainstay of life and education in general or only Islamic Religious Education, namely educational technology. This writing uses qualitative research analyzing directly, critically and comprehensively to existing sources, so as to obtain a learning method with an interactive model in its application later when in the world of education or related to Islamic Religion and in educational technology itself.